Genetic mutations that confer resistance to Isoniazid in patients with Tuberculosis in Lima Centro, Perú 2017- 2018 - Vargas-Ponce, Kenneth G. (2021)
This a report of the frequency of KatG and inhA genetic mutations that confer resistance to isoniazid in a sample of 777 patients with resistance to isoniazid. GenoType® MTBDRplus test and conventional sensitivity tests by the agar plate method were used. It was found that 54% presented mutation in the KatG gene, associated with higher resistance to streptomycin 76.6% (p <0.05), rifampicin 66.7% (p <0.05) and ethionamide in 33% (p <0.05). inhA gene mutation has a frequency of 46% and was associated with resistance to ethionamide in 68.1% (p <0.05), rifampicin 47.2% (p <0.05) and streptomycin 33% (p <0.05). In this sample, the presences of mutations that confer resistance to isoniazid was associated with resistance to other antituberculosis drugs.